Ruck-Play as performance indicator during the 2010 Six Nations Championship - Kraak, W. J.; Welman, K. E. (International Journal of Sports Science and Coaching, 2014)
The contest for possession has resulted in ball release delays. Accordingly the International Rugby Board amended the laws surrounding the ruck area in 2009. The study objective was to determine if a relationship exists between the ruck outcomes and ranking of the 2010 Six Nations Championship teams, establish differences between locations, compare the top to the bottom ranked teams and if the number of players involved influences ruck outcome. Fifteen 2010 Six Nations Championship matches were analysed by a performance analyst. Of the 1479 rucks, 92% retained the ball successfully, with no difference between the ruck success rate and team ranking, regardless if teams were attacking (p=0.74) or defending (p=0.95). Generally four players were involved during rucks. The players involved during unsuccessful and successful retention of the ball differed (p=0.03, d=0.21). Attackers involved mostly two players (50%), whereas defenders had typically one player (68%). Attacking teams were particularly successful, in retaining possession, if they had one more attacker involved than the defenders (p<0.05). Most rucks formed in zone B and fewer rucks were formed by top teams. Training programs should adapt to accommodate law changes.